Penyuluhan Literasi Digital Dalam Mencegah Perilaku Disinformasi Dalam Kehiduapan Bermasyarkat Pada Guru SMP - Wahyu Febri Ramadhan Sudirman; Hidayat Hidayat; Syafnur Muhammad Rizki; Muhammad Arif (Global Sustainability Research Institute, 2025)
This community service activity aims to improve the understanding and skills of digital literacy among junior high school (SMP) teachers, with a focus on the wise, safe, and ethical use of social media. In today's digital era, teachers' roles are not only as instructors in the classroom but also as role models in a healthy digital ecosystem. Through this outreach, participants were provided with an understanding of the basic concepts of digital literacy, the risks and challenges in the digital space, and strategies for using social media to support learning and shape student character. The activity's implementation methods included material delivery, interactive discussions, and case simulations. The results of the activity showed a significant increase in teachers' knowledge and awareness of the importance of digital literacy, as well as a change in attitudes toward more responsible online activities. This activity is expected to be the first step in building a positive digital culture in the school environment and encourage teachers to become agents of digital literacy amidst the rapid flow of digital information today.